Pengaruh Komitmen, Kompensasi Dan Konflik Terhadap Turnover Intention Karyawan (Studi Kasus Pada PT. Indo Metro Surya Andola Kota Metro) - Meta Ayu Ariska; Suwarto; Fitriani (Universitas Muhammadiyah Metro, 2025)
Turnover resulted in several losses for the company. Such as costs that must be borne andtime spent on recruitment, selection and training in order to get employees who have thesame quality as those who leave the company. The research was conducted with the aim ofknowing whether commitment, compensation and conflict simultaneously affect employeeturnover intention at PT. Indo Metro Surya Andola Metro City. The research method used isa quantitative method. Data collection used a questionnaire which was distributed to 38research samples. Testing the data using multiple linear regression with the help of the SPSSapplication. The results of the hypothesis test show that there is a negative and insignificanteffect of commitment on employee turnover intention at PT Indo Metro Surya Andola MetroCity. The research results show that the hypothesis test has a negative and insignificanteffect of compensation on employee turnover intention at PT Indo Metro Surya Andola MetroCity. The results of the hypothesis test show that there is a positive and significant conflicteffect on employee turnover intention at PT Indo Metro Surya Andola Metro City. Theresults of the hypothesis test show that there is a positive and significant effect ofcommitment, compensation and conflict on employee turnover intention at PT Indo MetroSurya Andola Metro City